PENGARUH LINGKUNGAN KERJA, FASILITAS KERJA DAN MOTIVASI TERHADAP KINERJA GURU DI YAYASAN PENDIDIKAN AZADIN ANHAR KECAMATAN WAMPU KABUPATEN LANGKAT - Heriati .; Putri Herviana Daulay (Jurnal Prodi Fakultas Ekonomi-UISU, 2020)
The formulation of the problem in this study is how the influence of the Work Environment, Work Facilities and Motivation on Teacher Performance at the Azadin Anhar Education Foundation, Wampu subdistrict, Langkat Regency, both partially and simultaneously. The population and sample of this study were all teachers at the foundation, amounting to 37 people. The sampling technique uses total sampling. Data collection techniques used were direct interviews and questionnaires. The results of this study are partially Work Environment variables have a positive and significant effect on Teacher Performance with tcount ttable, (5.525 2.04,), Work Facility variables have a positive and significant effect on Teacher Performance with tcount ttable, (2,411 2.04) and Motivational Variables have a positive and significant effect on Teacher Performance with tcount ttable, (3.218 2.04). Simultaneously the variable Work Environment, Work Facilities and Motivation have a positive and significant effect on Teacher Performance with Fcount Ftable, (14.558 2.87). R2 (RSquare) value of 0.540, which means that the variable Work Environment, Work Facilities and Motivation has a positive and significant effect on Teacher Performance at Azadin Anhar Education Foundation, Wampu Subdistrict, Langkat Regency by 54.00%, and the remaining 46.00%, influenced by other factors not examined.